2017
DOI: 10.23736/s0021-9509.16.09770-6
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic carotid artery stenosis: who should be screened, who should be treated and how should we treat them?

Abstract: Although stopping smoking, lowering blood pressure and reducing lipid levels will reduce global stroke risk and cardiovascular mortality, these remain leading causes of death and disability especially in ageing populations. Further prevention strategies are needed and, in the first part of this review, we explore the potential benefits of appropriate screening for carotid artery disease to reduce stroke and identify those who may have related cardiac disease. Although whole-population carotid screening is an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…There are no randomized control trials to compare the benefits of screening vs. no screening in the general population and the effect on rates of stroke and cardiovascular disease. Study suggests both medical and surgical interventions to reduce the risk of stroke in asymptomatic patients be effective 11 Nevertheless, the biggest problem is who will be screened 12 . In our study, we defined five more common modifiable risk factors among our population as inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…There are no randomized control trials to compare the benefits of screening vs. no screening in the general population and the effect on rates of stroke and cardiovascular disease. Study suggests both medical and surgical interventions to reduce the risk of stroke in asymptomatic patients be effective 11 Nevertheless, the biggest problem is who will be screened 12 . In our study, we defined five more common modifiable risk factors among our population as inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…The Report on the Prevention and Treatment of Stroke in China (2016) revealed that the prevalence of stroke in China increased from 0.4% in 1993 to 1.23% in 2013. The prevalence has continued to increase in recent years and stroke has become a critical disease that seriously impedes socio-economic development due to its high incidence, high recurrence rate, and high disability rate (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Philips US system Affiniti 70, L12-5 50 mm Linear Probe transducer was used. The Grey-Weale updated scale 28 , 29 , 30 , 31 , 32 and color Doppler imaging were used to characterize the carotid plaque. Peak systolic and end-diastolic velocities, and internal carotid artery/common carotid artery ratio, were registered.…”
Section: Methodsmentioning
confidence: 99%